Marshmallows, Fun, and Constellations: A Mixed-Methods Evaluation of a STEAM Astronomy Workshop - Iro Voulgari; Simeona Mamo; Edward Duca; Konstantinos Lavidas (STEAM Journal For Elementary School Education, 2025)
This study evaluates a STEAM-based astronomy workshop for children, delivered at two science engagement events in Malta: Science in the City 2023 and Unconventional Science Careers Days 2023. The workshop integrated storytelling, mythological narratives, creative making activities, and digital tools within the 5E instructional model and the creative pedagogy CREATIONS, with constellations as the central theme. Using a mixed-methods approach, we collected survey data from 122 participants (aged M=10, SD=2.4) and practitioner observations. Quantitative analysis showed that most children (80.3%) found the workshop easy to understand, though 91.8% reported not learning new content. Despite this, 51.6% expressed strong interest in learning more about astronomy, and 55.7% wanted similar school workshops. Significant differences emerged by setting: open-air festival participants reported higher levels of enjoyment and clarity than classroom-based participants. Qualitative analysis revealed children emphasized astronomy knowledge, enjoyment, and creative processes, often linking learning to personal contexts such as zodiac signs. Practitioner observations highlighted parental involvement as both supportive and potentially intrusive. These findings suggest STEAM workshops emphasising artistic processes, can stimulate curiosity, engagement, and cultural relevance in astronomy education, while underscoring the importance of facilitator training and careful scaffolding to balance creativity with conceptual accuracy. The study contributes to research on non-formal STEAM learning by demonstrating the potential and challenges of integrating arts, storytelling, and science in astronomy education.